Targeted lipidomics reveals a novel role for glucosylceramides in glucose response - Mark A. Xatse; Andre F.C. Vieira; Chloe Byrne; Carissa Perez Olsen (Journal of Lipid Research, 2023)
The addition of excess glucose to the diet drives a coordinated response of lipid metabolism pathways to tune the membrane composition to the altered diet. Here, we have employed targeted lipidomic approaches to quantify the specific changes in the phospholipid and sphingolipid populations that occur in elevated glucose conditions. The lipids within wild-type Caenorhabditis elegans are strikingly stable with no significant changes identified in our global mass spectrometry–based analysis. Previous work has identified ELO-5, an elongase that is critical for the synthesis of monomethyl branched-chain fatty acids (mmBCFAs), as essential for surviving elevated glucose conditions. Therefore, we performed targeted lipidomics on elo-5 RNAi-fed animals and identified several significant changes in these animals in lipid species that contain mmBCFAs as well as in species that do not contain mmBCFAs. Of particular note, we identified a specific glucosylceramide (GlcCer 17:1;O2/22:0;O) that is also significantly upregulated with glucose in wild-type animals. Furthermore, compromising the production of the glucosylceramide pool with elo-3 or cgt-3 RNAi leads to premature death in glucose-fed animals. Taken together, our lipid analysis has expanded the mechanistic understanding of metabolic rewiring with glucose feeding and has identified a new role for the GlcCer 17:1;O2/22:0;O.